EU policies on online entrepreneurship: Conversations with U.S. venture capitalists - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2013)
This paper examines the role of policy for creating an attractive atmosphere for venture capital investments in online start-ups and entrepreneurship. It is based on in-depth interviews with venture capitalists in the United States.The main takeaway points are: The policy atmosphere is important for Internet start-ups and online entrepreneurs. It is also important for investors and is likely to play an even more important role as regulations with a direct impact on online business grow and expand their scope. There is a difference between investors in how important they consider policy to be for investments in online entrepreneurship - how the policy atmosphere relates to other factors that are critical to success (e.g. access to capital, labour, et cetera). Most venture capitalists are critical of labour policy in Europe, and consider it to be one of the reasons why they are hesitant about investing money in European start-ups. The argument is that venture capitalists invest in companies with uncertain futures, and that the money they invest cannot be locked up in managing a work force that may not be the right one when a company need to change its course. (...)
Keywords: 330